2023
DOI: 10.1186/s13293-023-00564-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic hypogonadal mouse model reveals niche-specific influence of reproductive axis and sex on intestinal microbial communities

Laura Sisk-Hackworth,
Jada Brown,
Lillian Sau
et al.

Abstract: Background The gut microbiome has been linked to many diseases with sex bias including autoimmune, metabolic, neurological, and reproductive disorders. While numerous studies report sex differences in fecal microbial communities, the role of the reproductive axis in this differentiation is unclear and it is unknown how sex differentiation affects microbial diversity in specific regions of the small and large intestine. Methods We used a genetic hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…Members of the Lachnospiraceae, on the other hand, were more abundant in wild-type mice at peripuberty and adulthood compared to mutant mice, a result supported by a balance analysis that showed one specific genus of Lachnospiraceae to be more abundant in wild-type mice than mutant mice. Our previous study also found higher abundances of Lachnospiraceae in the cecum lumen of wild-type mice compared to mutant mice [65]. Studies have shown that Lachnospiraceae degrade host mucins and produce short-chain fatty acids that can affect host inflammation [66,67].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Members of the Lachnospiraceae, on the other hand, were more abundant in wild-type mice at peripuberty and adulthood compared to mutant mice, a result supported by a balance analysis that showed one specific genus of Lachnospiraceae to be more abundant in wild-type mice than mutant mice. Our previous study also found higher abundances of Lachnospiraceae in the cecum lumen of wild-type mice compared to mutant mice [65]. Studies have shown that Lachnospiraceae degrade host mucins and produce short-chain fatty acids that can affect host inflammation [66,67].…”
Section: Discussionmentioning
confidence: 67%
“…Bacteria in this family are known to degrade complex carbohydrate, including host mucins, and they are also know to contain genes for bile acid transformation [64]. Previous work showed that Muribaculaceae species were especially abundant in mutant adult mice in microbial communities of the small and large intestine [65]. Members of the Lachnospiraceae, on the other hand, were more abundant in wild-type mice at peripuberty and adulthood compared to mutant mice, a result supported by a balance analysis that showed one specific genus of Lachnospiraceae to be more abundant in wild-type mice than mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown that the sampling methods can impact on the diversity of microbial 15 , the effects of sampling methods on the intestinal microbial community composition and functional had rarely investigated systematically. This lack of research hinders our understanding of the complex interactions between the gut microbiome and human health.…”
Section: Discussionmentioning
confidence: 99%